Recrystallization kinetics of the AA5xxx series aluminum alloys - revisited. Issue 1 (1st July 2022) - Vandermeer, Roy; Lin, Fengxiang; Lei, Xiuchuan; Sanders, Robert Edward; Jensen, Dorte Juul
Abstract: In previous work [1], we analyzed the recrystallization kinetics in cold-rolled AA5657 and AA5182 based on measurements of the volume fraction of recrystallized material, the free (unimpinged) surface area density and the average size of the recrystallizing grains, plus the contiguity between recrystallizing grains, for a series of partially recrystallized samples. In that work, the calculated growth and nucleation rates were used as basis from the analysis. These two properties are derived from the measured parameters, which, as shown in the present work, adds to their uncertainty. In the present paper, we revisit the kinetics using improved stereological data and perform a full microstructural path analysis. The new analysis results are compared to the previous ones and the implications of using the different types of data sets and analytical approach for the interpretation of the kinetics are discussed.